Isolation, Identification and Characterization of a Feather Degrading Bacterium - Joshi, Savitha G.; Tejashwini, M.M.; Revati, N.; Sridevi, R.; Roma, D. (International Journal of Poultry Science, 2007)
Feather constitutes over 90% protein, the main component being beta-keratin, a fibrous and insoluble structural protein extensively cross linked by disulfide bonds. This renders them resistant to digestion by animal, insects and proteases leading to serious disposal problems. In addition to this, feather waste is produced at the rate of 22 million kg per year (US alone). Use of keratinolytic microorganisms for feather degradation is an economical, environmental friendly alternative. Keratinases which are produced by these keratinolytic organisms could be used to degrade feather waste and further the digested products could be an excellent material for producing animal feed, fertilizers or natural gas. A feather-degrading bacterium was isolated from poultry waste. This bacterium was grown in basal media with feathers as its primary source of carbon, nitrogen, sulfur and energy. The organism is rod shaped, highly motile, endospore forming, catalase positive and gram negative. Phenotypic characterization carried out in our laboratory showed that this novel gram negative bacterium belongs to Bacillus genus. The organism is designated as Bacillus and named as Bacillus sp PW-1. The isolated strain has activity of 50 U/ml. This novel keratinolytic isolate could be a potential candidate for degradation and utilization of feather keratin.